Evaluation of the Pharmacokinetics and Safety of a Single Dose of Acalabrutinib in Subjects With Hepatic Impairment. (15th February 2022) - Xu, Yan; Izumi, Raquel; Nguyen, Helen; Kwan, Anna; Kuo, Howard; Madere, Jeannine; Slatter, J. Greg; Podoll, Terry; Vishwanathan, Karthick; Marbury, Thomas; Smith, William; Preston, Richard A.; et al.
Abstract: Acalabrutinib received approval for the treatment of adult patients with mantle cell lymphoma who received at least 1 prior therapy and adult patients with chronic lymphocytic leukemia or small lymphocytic lymphoma. This study investigated the impact of hepatic impairment (HI) on acalabrutinib pharmacokinetics (PK) and safety at a single 50‐mg dose in fasted subjects. This study was divided into 2 parts: study 1, an open‐label, parallel‐group study in Child‐Pugh class A or B subjects and healthy subjects; and study 2, an open‐label, parallel‐group study in Child‐Pugh class C subjects and healthy subjects. Baseline characteristics and safety profiles were similar across groups. Acalabrutinib exposure (area under the plasma concentration–time curve) increased slightly (1.90‐ and 1.48‐fold) in subjects with mild (Child‐Pugh class A) and moderate (Child‐Pugh class B) hepatic impairment compared with healthy subjects. In severe hepatic impairment (Child‐Pugh class C), acalabrutinib exposure (area under the plasma concentration–time curve and maximum plasma concentration) increased ≈5.0‐ and 3.6‐fold, respectively. Results were consistent across total and unbound exposures. Severe hepatic impairment did not impact total/unbound metabolite (ACP‐5862) exposures; the metabolite‐to‐parent ratio decreased to 0.6 to 0.8 (vs 3.1‐3.6 in healthy subjects). In summary, single oral dose of 50‐mg acalabrutinib was safe and well tolerated in subjects with mild, moderate, and severe hepatic impairment and in healthy control subjects. In subjects with severe hepatic impairment, mean acalabrutinib exposure increased by up to 5‐fold and should be avoided. Acalabrutinib does not require dose adjustment in patients with mild or moderate hepatic impairment.